Dataset of 16S ribosomal DNA sequences of bacteria isolated from marine red algae Kappapycus alvarezii - Rennielyn Rupert; Kenneth Francis Rodrigues; Chong, Harry Lye Hin; Wilson Thau Lym Yong (Elsevier Inc., 2022)
The data provided in the article contains bacterial commu- nity profiles present on the surface of red algae ( Kappa- phycus alvarezii ) isolated directly after collection and after 30 days of cultivation in a closed circulation system. The ex- plants of Kappaphycus alvarezii were cultivated in a labora- tory setting under controlled growth conditions for 30 days in order to determine bacteria that could adapt to controlled culture conditions. Amplification and sequencing of bacterial 16S rDNA amplicon were performed on bacterial isolates as- sociated with the seedlings. The 16S rDNA gene sequences were analyzed, trimmed, and assembled into contigs using DNA Baser Sequence Assembler (V5) software. Taxonomic identification for the assembled sequences was achieved us- ing the online BLAST (blastn) algorithm, and the construction of a phylogenetic tree was performed using the MEGA7 soft- ware. The data reveals a distinct set of microbial variations between day one and day 30. The phylogenetic tree depicts four major clusters, Vibrio, Pseudoalteromonas, Alteromonas , and Bacterioplanes resident on the surface of the K. alvarezii . Comparison between these two bacterial groups provides ev- idence of the persistent marine bacteria that adapt to the long-term culture in closed circulation systems. Raw data files are available at the GenBank, NCBI database under the accession number of MZ570560 to MZ570580.